EFISIENSI ANGGARAN BELANJA DAERAH PADA KECAMATAN KOTAPINANG LABUHANBATU SELATAN TAHUN 2017-2019 - Yulia Kasih Nasution (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2022)
This research was conducted in Kotapinang District and aims to find out how much the measurement of the efficiency of regional spending in increasing district income by using efficiency theory according to Mahmudi (2015:85). And descriptive research method with a qualitative approach. The results of this study show that (1) The level of measurement of the efficiency of the Kotapinang District budget for 2017-2019 is categorized as Efficient with the average measurement level below 100%. (2) The implementation of Regional Expenditures has been quite optimal because Kotapinang District has been able to realize the budget properly. (3) The suitability of Budget Realization with Programs/Activities has not been optimal due to lack of initial planning, Leadership Management looks at the previous year's Document. (4) Human Resources in Kotapinang Sub-district are not optimal because there are still insufficient human resources, both in terms of quality and quantity.Budget, Efficiency, Regional Expenditure